Is long period time charters still a viable option in today's market conditions? - Tan, Darren Qin Tian (2018)
Decision to engage in different charter types has been a revolving question for shipowners, especially in the dry bulk market, due to the ever-changing environment and cyclical nature of the shipping market. This report aims to answer the relevance and profitability of long-term time charter in today’s market for shipowners with a focus on Capesize market. Many research and studies casted spotlight on non-bulk market while leaving dry bulk Capesize market in the background. In light of this, the report also aims to bridge this gap by reviewing various factors affecting Capesize spot rates and examining the feasibility of long-term time charter, leading to a conclusive recommendation. This report is supported by two quantitative models namely Triple Exponential Smoothing (TES) and Linear Regression (LR) where historical data retrieved from multiple databases are inputted to generate forecasts. Results showed that long-term Capesize time charter is viable if future charter hire rises 76% above current levels. This is a shockingly high increment but with the uncertainties and volatility of the shipping market, this may not be impossible after all.